Induction of spermatogenesis in men with hypogonadotropic hypogonadism - Morris, Guy C. (J Assist Reprod Genet, 2021)
PURPOSE: We compared our clinical experience to international standards, assessed by response to treatment and pregnancy rates to ensure our results were comparable. METHODS: Men presenting with azoospermia related to hypogonadism were recruited into a treatment programme which was managed by one person over 8 years in a secondary care facility. Treatment followed published management plans using urinary gonadotropins. Data were collected on success rates in spermatogenesis, as well as variables which might predict success, and costs. Statistical analysis used non-parametric methods. RESULTS: Of 16 men with HH, 14 achieved spermatogenesis, and 9 had sperm cryopreserved. Of those 14, 6 were successful in achieving a pregnancy with their partner from assisted conception (including ICSI) and one after natural conception. Factors identified to identify men likely to be successful in treatment were whether testicular volume was larger at onset of gonadotropins (median 10 mL) with a trend towards greater success if the cause developed after puberty. Mean treatment costs per man treated amounted to GP£4379/UD$5377 (figures for September 2020). SUMMARY: Success rates from this treatment should exceed 70% in most clinical settings. The likelihood of success improves when testicular volume exceeded 10 mL at initiation of treatment and a trend exists whereby success is more likely whereby when hypogonadism developed after puberty. Treatment costs are at a level likely to benefit quality of life, supporting the delivery of this treatment and where necessary and possible, funding it in line with other fertility treatments. This treatment should be available much more widely as a management option for men with hypogonadism, allowing them to father a biological child, rather than using donor sperm.